THE WOUND HEALING PROPERTY OF THYME OLEORESIN FROM THYMUS VULGARIS L. ON HACAT KERATINOCYTES - Anitha, Roy; Subeeksha, V .s; Lakshmi, Thangavelu (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the present study was to evaluate the wound healing property of thyme oleoresin using HaCaT keratinocytes. Methods: The effect of thyme oleoresin on cell migratory activity of HaCaT keratinocytes was investigated and analyzed using scratch assay. The HaCaT cell line was obtained from NCCS Pune and maintained in Dulbecco's Modified Eagle's Media. The keratinocyte cells (HaCaT) were trypsinized for 30 s and passaged to T25 flasks in complete aseptic environment. The effect of thyme oleoresin on wound closure was determined using a 12-well plate. Dulbecco's Modified Eagle's medium with dimethyl sulfoxide was used as control. The effect of thyme oleoresin on wound closure was determined microscopically at 20Ã— magnification using Nikon microscope. The experiment was performed in triplicate. The wound area was photographed and analyzed. Results: Thyme oleoresin at 25 Î¼g/ml and 50 Î¼g/ml has significantly promoted the migration of HaCaT cells, thereby leading to wound closure. Conclusion: The study has proved the wound healing property of thyme oleoresin, and hence, it may be used for wound healing purpose in a natural way.